PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Mega Putri Yustia Sari; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
Sustainability report disclosure in Indonesia has left the initial phase. Now the number of corporate that reveal sustainability report is increasing from the previous period. The aim of this research is to examine the effects of financial performances, firm size and corporate governance to the sustainability report disclosure. The population of this research is listed companies in the BEI (Bursa Efek Indonesia) in the year 2009-2011. The selection of this sample uses purposive sampling method. Based on purposive sampling method, the samples of firms that publish sustainability report are 23 companies. Results of this research indicate that audit committee and board of commissioner independence have a positive effect on sustainability report disclosure. The profitability variable have a negative effect on sustainability report. While liquidity, leverage, firm activity, firm size and board of director showed no effect on sustainability report disclosure. The results showed that financial performances have not full effect to the sustainability report.